Adenosine Triphosphate Release is Required for Toll-Like Receptor-Induced Monocyte/Macrophage Activation, Inflammasome Signaling, Interleukin-1β Production, and the Host Immune Response to Infection - Lee, Albert H; Ledderose, Carola; Li, Xiaoou; Slubowski, Christian J; Sueyoshi, Koichiro; Staudenmaier, Laura; Bao, Yi; Zhang, Jingping; Junger, Wolfgang G (Critical care medicine, 2018)
Monocytes and macrophages produce interleukin-1β by inflammasome activation which involves adenosine triphosphate release, pannexin-1 channels, and P2X7 receptors. However, interleukin-1β can also be produced in an inflammasome-independent fashion. Here we studied if this mechanism also involves adenosine triphosphate signaling and how it contributes to inflammasome activation. In vitro studies with human cells and randomized animal experiments. Preclinical academic research laboratory. Wild-type C57BL/6 and pannexin-1 knockout mice, healthy human subjects for cell isolation. Human monocytes and U937 macrophages were treated with different inhibitors to study how purinergic signaling contributes to toll-like receptor-induced cell activation and interleukin-1β production. Wild-type and pannexin-1 knockout mice were subjected to cecal ligation and puncture to study the role of purinergic signaling in interleukin-1β production and host immune defense. Toll-like receptor agonists triggered mitochondrial adenosine triphosphate production and adenosine triphosphate release within seconds. Inhibition of mitochondria, adenosine triphosphate release, or P2 receptors blocked p38 mitogen-activated protein kinase and caspase-1 activation and interleukin-1β secretion. Mice lacking pannexin-1 failed to activate monocytes, to produce interleukin-1β, and to effectively clear bacteria following cecal ligation and puncture. Purinergic signaling has two separate roles in monocyte/macrophage activation, namely to facilitate the initial detection of danger signals via toll-like receptors and subsequently to regulate nucleotide-binding oligomerization domain, leucine rich repeat and pyrin domain containing 3 inflammasome activation. Further dissection of these mechanisms may reveal novel therapeutic targets for immunomodulation in critical care patients.